Iridium‐Catalyzed Reductive Alkylations of Secondary Amides - Ou, Wei; Han, Feng; Hu, Xiu‐Ning; Chen, Hang; Huang, Pei‐Qiang (Angewandte Chemie International Edition, 2018)
Reported herein is the first direct, metal‐catalyzed reductive functionalization of secondary amides to give functionalized amines and heterocycles. The method is shown to have exceptionally broad scope with respect to suitable nucleophiles, which cover both hard and soft C nucleophiles as well as a P nucleophile. The reaction exhibits good chemoselectivity and tolerates several sensitive functional groups. A soft touch: A versatile, direct, metal‐catalyzed reductive functionalization reaction of secondary amides, to give functionalized amines and heterocycles, was developed. A broad substrate scope for both the amide and nucleophile was observed. Viable nucleophiles include reactive and soft C nucleophiles as well as a P nucleophile. The reaction exhibits good chemoselectivity and tolerates several sensitive functional groups (FGs).